2016
DOI: 10.21577/0103-5053.20160213
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites Based on Cassava Starch and Chitosan-Modified Clay: Physico‑Mechanical Properties and Biodegradability in Simulated Compost Soil

Abstract: Organic-inorganic nanocomposites based on cassava starch, glycerol and chitosan-modified Veegum ® HS clay mineral at two different low polymer-to-clay ratios (2.5 and 5.0 wt.%) were prepared by extrusion producing flexible, transparent and homogeneous plastics as potential candidates for agricultural purposes. X-ray diffraction and transmission electron microscopy images revealed the presence of both intercalated and exfoliated nanocomposites in all samples, in which exfoliation is the predominant type of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
3
7
0
1
Order By: Relevance
“…Similarly, the blank and GM-loaded films exhibited three-step thermal degradation, but the onset temperatures of the second and third steps of films were lower as compared to that of AX (Table S1). This change in onset temperature appears to be due the presence of glycerol (decomposes at approximately 160 °C) [38]. The onset of the second and third steps increased with the AX content of the films, which clearly supports the argument that the lowering of the decomposition temperature of the film was due to the presence of glycerol.…”
Section: Thermal Analysissupporting
confidence: 73%
“…Similarly, the blank and GM-loaded films exhibited three-step thermal degradation, but the onset temperatures of the second and third steps of films were lower as compared to that of AX (Table S1). This change in onset temperature appears to be due the presence of glycerol (decomposes at approximately 160 °C) [38]. The onset of the second and third steps increased with the AX content of the films, which clearly supports the argument that the lowering of the decomposition temperature of the film was due to the presence of glycerol.…”
Section: Thermal Analysissupporting
confidence: 73%
“…The Figure 5 shows derivative thermogravimetric curves (DTG) of SPI, PHB, and the bilayer films. All bilayer and pure SPI films presented a peak at around 50 C, related to water content desorption, and the peak of glycerol evaporation from SPI matrix at around 150-270 C. 42,43 SPI degradation range was located from 270 to 500 C in all bilayer films thermograms. 42 DTG curves of the bilayer SPI/12PHB and pristine PHB films showed a peak at around 240-270 C attributed to PHB degradation.…”
Section: Thermal and Mechanical Characterizationmentioning
confidence: 95%
“…All bilayer and pure SPI films presented a peak at around 50 C, related to water content desorption, and the peak of glycerol evaporation from SPI matrix at around 150-270 C. 42,43 SPI degradation range was located from 270 to 500 C in all bilayer films thermograms. 42 DTG curves of the bilayer SPI/12PHB and pristine PHB films showed a peak at around 240-270 C attributed to PHB degradation. 41 In SPI/8PHB and SPI/10PHB films the above mentioned peak is difficult to observe due to glycerol evaporation peak overlapping.…”
Section: Thermal and Mechanical Characterizationmentioning
confidence: 95%
“…Iftekhar et al [11] used a XANT-layered double hydroxide nanocomposite to remove metal ions from rare earth elements, obtaining good maxima adsorption capacities (Sc +3 : Qo = 132.30 mg/g, Nd +3 : Qo = 14.01 mg/g, Tm +3 : Qo = 18.15 mg/g, and Yb +3 : Qo = 25.73 mg/g) and finally it has been reported that organic compounds such as trichloroethylene was transformed (65 % from an aqueous solution containing 10 mg/L of this compound) by XANT-zero valent iron particles [12], and bisphenol A was adsorbed by the temperature-sensitive XANT-isopropylacrylamide hydrogel with a high efficiency (Qo = 458 mg/g) [13]. Nonetheless, the XANT-derivatization or synthesis of nanocomposites demand a considerable cost in reagents and energy, and the biodegradability of these compounds is decreased [36][37][38].…”
Section: Introductionmentioning
confidence: 99%